Efektivitas Penerapan Presensi Kehadiran ASN Di Dinas Perhubungan Kabupaten Malang Provinsi Jawa Timur - Shelsabilla Regyna A (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Currently, technological advances are very rapid and sophisticated. It is not surprising that this progress is utilized by many sectors, both private and government. The government must use technology to develop more sophisticated and inventive government systems. One of them is a unique finger impression-based attendance method that is used to discipline employees in carrying out their duties. The purpose of this research is to find out how effective the use of unique finger impressions is to discipline employees at the Malang Regency Transportation Service, how effective the use of unique finger impressions is to increase employee discipline, and the steps taken to improve employee discipline. This study is based on an inductive approach combined with a descriptive approach. Data collection methods include interviews, observation, and documentation. According to Tangkilisan (2005: 141), there are four ways to evaluate effectiveness: target achievement, adaptability, job satisfaction, and responsibility. By using unique finger impressions, employee discipline and organizational performance improve. However, there are several challenges, one of which is that employees continue to come for unique finger impressions rather than performance, which hinders them from completing tasks on time. One of the efforts made by the Malang Regency Transportation Service is to carry out direct supervision from the leadership and apply disciplinary penalties objectively and according to procedures. The author suggests improving or updating unique fingerprint scanning machine technology, especially the sensitivity of the scanner in reading fingerprints, and adding one unit of unique fingerprint scanning machine